Relationship Between Family Support and Psychological Response to Chronic Kidney Failure Patients - Windu Santoso; Sri Sudarsih (Universitas Aisyah Pringsewu, 2021)
Chronic renal failure patients undergoing hemodialysis may exhibit a variety of psychological responses. One of the factors that influence it is family support. This study aimed to determine the relationship between family support and the psychological response of chronic renal failure patients undergoing hemodialysis. The research design used correlation analysis with a cross-sectional approach. Samples were chronic renal failure patients undergoing hemodialysis (n = 183) with consecutive sampling. The data collection used a family support questionnaire and a psychological response questionnaire. Data analysis used the Spearman rank test. The results showed that dominant family support was quite high (72.1%). A small proportion of respondents had a psychological response to acceptance (38.8%). There is no relationship between family support and psychological response (p = 0.26 more than 0.05). Family support does not affect the psychological response, but considering that hemodialysis therapy is very long, family support must still be given optimally.